The Challenges and Opportunities of Digitalization in Islamic Religious Education Institutions - Ciptadi, Teguh; Khozin (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study examines the challenges, opportunities, and resource readiness in the digitalization of Islamic Religious Education (PAI) institutions at SMA Negeri 1 Bulik. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The results show that the main challenges include limited infrastructure and the digital competency of teachers, while students' enthusiasm for technology presents significant opportunities. Human resources exhibit varying levels of readiness, requiring intensive training. Digitalization has not yet been optimally integrated into the curriculum but holds great potential to support interactive learning. This study contributes theoretically by emphasizing the role of students as actors in digital transformation and offers practical recommendations for improving education policies. The findings pave the way for further research to explore the broader and deeper impacts of digitalization.